Identification of cold-responsive miRNAs in rats by deep sequencing. (May 2017) - Zhen, Li; Guo, Wenjin; Peng, Mengling; Liu, Yanzhi; Zang, Shucheng; Ji, Hong; Li, Shize; Yang, Huanmin
Abstract: miRNA is an endogenously noncoding sRNA, which is involved in post-transcription gene expression regulation of growth, tumor development and stress survival. As a biological marker, miRNA has been used for the early diagnosis of diseases and the evaluation of some physiological state. We constructed two small RNA libraries with the serums of rats treated or not with cold conditions (4 ℃ for 12 h) by deep sequencing, in order to understand the miRNAs' expressions of cold-exposed rats and find new cold-responsive biological markers. 485 conserved miRNAs and 287 novel miRNAs were identified in the two libraries by comparing to the known miRNAs of rat in miRBase 21.0 Differential expression analysis showed that 56 conserved miRNAs and 3 novel miRNAs were expressed differentially in low ambient temperature. The qRT-PCR results confirmed that rno-miR-151-3p, rno-miR-210-3p, rno-miR-425-5p, rno-miR-383-5p, rno-miR-92a-3p, rno-miR-98-5p and rno-miR-328a-3p decreased significantly in rats serums treated with cold exposure. The expressions of the 7 miRNAs changed significantly in cold-exposed rats' livers too. rno-miR-383-5p decreased significantly, but all the others increased significantly. Thus, the 7 miRNAs were considered as cold-responsive miRNAs of rat. 670 target genes of the 7 cold-responsive miRNAs were predicted. KEGG analysis showed that they were enriched in 28 pathways and most of them were enriched by metabolic pathway. Overall, the results of this study suggest an important role for selected miRNA's in the response to cold stress. Highlights: 485 conserved miRNAs are identified in rat serum. 287 novel miRNAs are identified in rat serum. 56 differentially expressed miRNAs are identified in cold stressed rat serum. 7 cold-responsive miRNAs are identified in rat serum and liver. The pathway that is most enriched by the target genes of the 7 cold-responsive miRNAs is metabolic pathways.